The Identification of Sport Talents Using a Sport Search - Ridwan Sinurat; Tofikin Tofikin (STKIP Muhammadiyah Kuningan, 2021)
This study aims to identify students who have talent based on the results of the talent analysis conducted at SMP 1 Rambah Rokan Hulu. This research method is a quantitative descriptive method. The data analysis technique used was sports test tracing. The sampling technique used was purposive sampling technique, meanwhile the samples determined by the researcher were students who like to exercise and are interested and willing to take part in this research. Based on these criteria, the sample size is 30 people. The results showed that 6.7% of children have shown their talent in long-distance running, 16.7% of children showed their talent in the sport of Judo, 6.7% of the children were gifted in the sport of rock climbing, 23.3% of the children showed their talent fast running, 23.3 % of children in street sports, 3.3% of children in Steeppleechase, 3.3% of children in hurdling, 3.3% of children in high jump and 13.3% of children in multi-jump sports respectively.